PEMANFAATAN RADIASI GAMMA Co-60 DALAM PEMULIAAN TANAMAN TOMAT (Lycopersicon esculentum L.) DENGAN METODE MUTAGEN FISIK - Ari Kusuma Putra, I Gusti Agung Ngurah; Sutapa, I Gusti Ngurah; Antha Kasmawan, I Gde (BULETIN FISIKA; Vol 18 No 1 (2017): BULETIN FISIKA, 2017)
A research on Co-60 gamma radiation effect of induced mutation in physiological growth of tomato plant (Lycopersicon Esculentum L.) has been done. Tomato plant quality can be improved through induced mutation Co-60 gamma radiation. Genetic change could be caused by induced mutation from radioactive material as a human effort. IRPASENA plant with Co-60 gamma radiation source exposed with dosage treatment of 50 Gy, 100 Gy, 150 Gy, 200 Gy and 250 Gy in tomato seeds. The measurement carried out against the physiological growth of plant height, leaves width, amount and weight of tomato fruits at the first week until harvest time. Result shows that the correct radiation dosage for tomato breeding is 100 Gy. Radioactivity concentration in improved tomato fruits after radiation exposure is less than 1.00 Bq/kg. Vitamins content on improved tomato fruits after exposure, particularly on vitamin C is 130.000 mg/kg compared to control fruit that is 70.000 mg/kg, the vitamin B1 also shows increased value (0.63 mg/kg) compared with control fruit (0.496%) .